Effect of Soy Isoflavones on the Serum Lipid Profile and Vascular Function - Helen C.D. Tuhumury (AGRITEKNO: Jurnal Teknologi Pertanian, 2015)
Soybeans are unique among the legumes because they are a concentrated source of isoflavones. A number of components of soy have been studied to investigate their potential effect on CVD. Soy proteins have been shown to lower LDL-cholesterol and to have neutral or slightly positive effect on HDL-cholesterol. However, to what extend actually is the role of the isoflavone in this action remained contradictive. This review describes the characteristics and the nature of the soy isoflavones as well as covering the results from several studies to determine the effect of soy isoflavones on the serum lipid and vascular functions.